The insertion of neogothic architecture in Mexico’s cultural heritage. - Pantoja Hernández, Samantha (Restauro Compás y Canto S.A., 2021)
The present research focuses in the Mexican neogothic architecture from a built heritage point of view. Buildings of this architectural trend comprise a variety of material, urban and social conditions, making a challenging task to include them in the present national politics of conservation. As a result, in the country these monuments can be found in diverse states, from recently concluded to notoriously damaged. This article’s main purpose is to demonstrate neogothic architecture’s value as Mexican patrimony through the analysis of its process of transculturation. The study englobes the period since the arrival of the architectural style to Mexico in 1850 until 2019, focusing on those examples located at the states of Guanajuato and Mexico City. According to this research’s findings, the neogothic buildings’ historical values, added to its adaptation to the local territory and social context and its appropriation from the Mexican people, qualifies this architecture as part of the country’s cultural heritage.